The 2004 Hurricane Season and Its Impact on Florida Wildlife Rehabilitators - Fox, Wendy (Wildlife Rehabilitation Bulletin, 2004)
The annual hurricane season in Florida is a fact of life. In May, you notice that the supermarket grocery bags are printed with hurricane tracking maps and that the local TV stations are giving out books entitled, “How to Prepare for Hurricane Season.” Newcomers to south Florida are a little uneasy, and old-timers talk about the great storms of years gone by. You do a mental check of the shutters and “guess” that the bolts are “somewhere in a baggie.” Still, nothing could prepare us for what happened this year. In August and September we had a steady stream of unwanted visitors: Charley, Frances, Ivan, and Jeanne. While the storms made landfall in different regions, hurricane and tropical storm-force winds and rain wreaked havoc from north to south each time. Mountains of information are available on how to prepare your home and your family for a “significant weather event,” a favorite term of one of our local weathermen. For wildlife rehabilitators, the challenges are many and magnified. You must not only worry about your home, but also about your facility, be it on your property or elsewhere.